Sex and age differences in the association between routine suicide newspaper reporting and change in admissions of suicidal patients: An investigation at an emergency and critical care center in Tokyo - Yasushi Emura; Sho Kanata; Naoki Hayashi; Ken-ichi Matsumura; Akihisa Akahane; Mamoru Tochigi; Hiroshi Kunugi (PLoS ONE, 2025)
Background The influence of media reporting on suicide and suicide attempts (SA) has been rigorously studied. Previous studies focused on characteristics like celebrity status, sex and age of suicide decedents, which may facilitate suicide and SA occurrence. These studies have informed guidelines for responsible media reporting. However, the nuanced effects on different sex and age groups of suicidal individuals remain less understood. Methods This study examined the association between the characteristics of initial suicide reports in four major newspapers and the differences in admission numbers (Δs) of SA patients across sex and age groups during pre- and post-article release one-week periods. Data from an Emergency and Critical Care Center from 2012 to 2019 were obtained through a review of medical records. Nonparametric MANOVAs were employed to investigate Δs for sex and age groups of SA patients in relation to sex and age of suicide decedents, incident types, and methods. Significant differences were evaluated using Wilcoxon tests. Results A total of 1,205 articles on 676 suicide incidents and 1,081 SA admissions were analyzed. MANOVAs revealed a significant association between the Δs and the reported suicide methods. Δ for females was positively associated with reports of gas poisoning and other infrequently reported methods, whereas Δ for males was negatively associated with gas poisoning. Δ for younger patients was positively associated with infrequently reported methods and negatively with firearm discharge. No significant associations were found between Δ and sex and age of decedents or incident types. Discussion This study demonstrates a differential impact of suicide news articles reporting gas poisoning, infrequently reported suicide methods, and firearm discharge, on SA patient admissions across sex and age groups. These differences may arise from variations in emotional responses to the suicide methods, which can be understood in both psychological and socio-cultural contexts. Further research is needed to clarify the determinants of differential influences to more effectively address and mitigate the risks of suicide and SAs.